2023
DOI: 10.1002/advs.202207488
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Tumor Suppression via Macrophage‐Driven Automated Homing of Metal‐Phenolic‐Gated Nanosponges for Metastatic Melanoma

Abstract: Cell-based therapies comprising the administration of living cells to patients for direct therapeutic activities have experienced remarkable success in the clinic, of which macrophages hold great potential for targeted drug delivery due to their inherent chemotactic mobility and homing ability to tumors with high efficiency. However, such targeted delivery of drugs through cellular systems remains a significant challenge due to the complexity of balancing high drugloading with high accumulations in solid tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…183 Furthermore, the metal-driven coordination of phenolic moieties also facilitates the interfacial assembly of colloidal building blocks on the secondary substrates. This polyphenol-based modular approach provides a versatile platform for the construction of complex functional supraparticles, 184,185 therapeutically engineered cells, 186,187 and photo-driven biohybrids for chemical production. 188 Polyphenols are promising precursors for the preparation of CS-SACs due to their rich catechol and/or galloyl groups in structure and low price.…”
Section: Aromatic Compoundsmentioning
confidence: 99%
“…183 Furthermore, the metal-driven coordination of phenolic moieties also facilitates the interfacial assembly of colloidal building blocks on the secondary substrates. This polyphenol-based modular approach provides a versatile platform for the construction of complex functional supraparticles, 184,185 therapeutically engineered cells, 186,187 and photo-driven biohybrids for chemical production. 188 Polyphenols are promising precursors for the preparation of CS-SACs due to their rich catechol and/or galloyl groups in structure and low price.…”
Section: Aromatic Compoundsmentioning
confidence: 99%
“…Hence, nature provides a diverse range of components for the design of “living devices” with varying degrees of cognition and capability to perform biological functions. While the interest in exploiting the functional advantages of biological colloids is growing, microrobotics based on living organisms faces a grand challengethe need for a versatile tool for the precise spatial manipulation of nonmagnetic living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have previously demonstrated that MPNs can form biomimetic nanocloaks on the surface of individual bacteria, [24] yeast, [25] and mammalian cells. [26,27] Importantly, MPN coatings can also encapsulate various proteins, polysaccharides, and other functional cargos, due to their high affinity with biomolecules. [28][29][30] MPNs thereby exhibit the potential to preserve all the signaling and recognition biomolecules once cloaked on cancer cells.…”
Section: Introductionmentioning
confidence: 99%